Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage terhadap Manajemen Laba Perusahaan Manufaktur (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Industri Makanan dan Minuman yang Terdaftar di BEI Periode 2021-2023) - Jehadut, Mariana; Mujiyono, Mujiyono (Innovative: Journal Of Social Science Research, 2025)
This study was conducted with the aim of determining how profitability, company size, and leverage affect earnings management in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample in this study was based on the purposive sampling method, namely a sampling technique with certain criteria. In this study, the number of samples studied was 25 companies. The research approach used was multiple linear regression analysis, with data obtained from the annual reports of companies listed on the IDX. The results of the study show that profitability, company size, and leverage have a significant positive effect on earnings management. These findings provide important insights for management, investors, stakeholders and readers to be able to determine the relationship between profitability, company size and leverage on earnings management.